P II – 2–7 No2 but not pm2.5 at the home address is associated with concern over health effects of air pollution. (18th March 2018) - Dons, Evi; Laeremans, Michelle; Anaya, Esther; Avila-Palencia, Ione; Nazelle, Audrey de; Gaupp-Berghausen, Mailin; Götschi, Thomas; Nieuwenhuijsen, Mark; Orjuela, Juan Pablo; Raser, Elisabeth; Standaert, Arnout; Panis, Luc Int
Abstract : Background/aim: People living in urban areas in Europe are exposed to elevated concentrations of air pollution. The lower the air pollution levels, the better for your health; so people exposed to higher concentrations should be worried more about air pollution. The aim of this analysis was to examine associations between concern over health effects of air pollution and personal and environmental factors. Methods: In 7 European cities, >12 000 participants over 18 years were recruited to complete an online questionnaire on travel and physical activity behaviour, perceptions and attitudes, and sociodemographics. The following question was assessed on a 5-point scale: 'Are you worried that air pollution in the neighbourhood of either your home or work can lead to health problems?' Mixed effects logistic regression was used to model concern over health effects of air pollution (worried (level 4–5) versus not-worried (level 1–3); city as random effect). Air pollution at the home address was determined using the West-European PM2.5 and NO2 land use regression models from de Hoogh et al. (2016). Potential confounding variables were chosen based on previous studies, and most variables were self-reported. Results: 57% of participants were worried over health effects of air pollution with large differences across cities (Antwerp 77%; Barcelona 81%; London 64%; Oerebro 12%; Rome 72%; Vienna 43%; Zurich 34%). Linking mean modelled air pollution to mean level of concern per city, gave a good correlation for NO2 (r²=0.75) and a lower correlation for PM2.5 (r²=0.49). In bivariate analyses, city, sex, education level, self-reported health, having children in the household, distance to the nearest major road, physical activity level, and NO2 and PM2.5 at home were significantly linked to concern over health effects of air pollution. In the mixed effects logistic regression model sex, self-reported health, having children in the household, physical activity level, and NO2 at home remained significant. Conclusion: Being male, having a worse self-reported health, having children in the household, being more physically active, and higher NO2 at the home address were associated with higher concern over health effects of air pollution.